Corridor light that blink on detecting motion / Muhammad Fajrul Jafrim & Ahmad Aslam Ismail - Jafrim, Muhammad Fajrul; Ismail, Ahmad Aslam (2015)
Nowadays, electrical energy that been consumpt during night are very high in whole wide world. Although there are many ways to save energy consumption to do so. Lights are one of the most high energy consumption during night . Usually we will use manual switch to on and off lights, but what if it can automatically on and off at certain circumstance during the night In this project, the main purpose to design automatic light corridor that will switch on by detecting motion. The PIR sensor will be use in this circuit to sense moving object. The circuit are design to to be fully functional during night and in daylight circuit will automatically set to idle by using LDR. The sensitivity of the LDR will be set for the circuit to differentiate between daylight and night. PIR sensor frequency will be set to detect motion. The sensor will be attach at corridor ceiling along with 3 LED and LDR will be at the top of the roof. Two led with low power consumption will be set at each corridor edge as passive light that only on during night. We are using 3 sensor, 5 LED and 1 LDR.